PSYCHOLOGICAL PREPARATION AS AN IMPROVEMENT FACTOR OF SPECIAL PHYSICAL TRAINING OF QUALIFIED VOLLEYBALL PLAYERS - Kyrylo Ponomarenko (Scientific Journal of Polonia University, 2025)
The article is devoted to the analysis of the influence of psychological preparation on the specialized training process of qualified volleyball players. The study used a comprehensive approach, which included a thorough analysis of psychological and pedagogical literature - the study of scientific papers, articles and other sources of information on the problem under study, as well as analytical work with information sources - synthesis and systematization of the knowledge gained, a clear formulation of key concepts and aspects of the topic. The author notes that the psychological training of athletes includes the formation of the ability to control their psychological state, effectively respond to stress factors and maintain emotional stability, which is crucial for the success of training and competition. It is substantiated that the development of an effective system of psychological training of volleyball players is critical to ensure their resistance to psychological challenges that arise during the game. In order to optimize the psychological climate in a sports team and increase the effectiveness of psychological training of qualified volleyball players, a set of psychological and pedagogical measures has been developed, including psychological education, methods of indirect influence, training in self-regulation methods, relaxation and recovery techniques, formation of pre-competitive rituals, psychological counseling and psychotherapy (if necessary), trainings, individual approach, interaction between a coach and a psychologist. The results obtained may be useful for coaches, sports psychologists, volleyball players and other interested parties.